The Evidence for a Causal Link Between Disease and Damaging Behavior in Pigs - Boyle, Laura A.; Edwards, Sandra A.; Bolhuis, J. Elizabeth; Pol, Françoise; Šemrov, Manja Zupan; Schütze, Sabine; Nordgreen, Janicke; Bozakova, Nadya; Sossidou, Evangelia N.; Valros, Anna (Frontiers in Veterinary Science, 2022)
Damaging behaviors such as tail biting, but also ear and flank biting, are prevalent in pig production and lead to reduced welfare and performance. Anecdotal reports suggest that health challenges increase the risk of tail biting. There are many common risk factors for tail biting and health problems, notably respiratory, enteric and locomotory diseases. These include suboptimal thermal climate, hygiene, stocking density and feed quality. The prevalence of tail damage and health problems also show high correlations across batches within and between farms. Limited evidence supports two likely causal mechanisms for a link between damaging behavior and health problems. The first is that generalized poor health (e.g. enzootic pneumonia) on farm poses an increased risk of pigs performing damaging behavior. Recent studies indicate a possible causal link between an experimental inflammation and an increase in tail biting-related behavior, and suggest a link between cytokines and tail biting. The negative effects of poor health on the ingestion and processing of nutrients means that immune-stimulated pigs may develop specific nutrient deficiencies, increasing tail biting. The second causal mechanism involves tail biting causing poor health. Indirectly, pathogens enter the body via the tail lesion and once infected, systemic spread of infection may occur, mainly via the venous route targeting the lungs, and to a lesser extent via cerebrospinal fluid and the lymphatic system. In carcasses with tail lesions, there is an increase in lung lesions, abscessation, arthritis and osteomyelitis. There is also evidence for the direct spread of pathogens between biters and victims. In summary, the literature supports the association between poor health and tail biting. However, there is not enough evidence to confirm causality in either direction. Nevertheless, the limited evidence is compelling enough to suggest that improvements to management and housing to enhance pig health will reduce damaging behavior. In the same way, improvements to housing and management designed to address problems with damaging behavior, are likely to result in benefits to pig health. While most of the available literature relates to tail biting, we suggest that similar mechanisms are responsible for links between health and other damaging behaviors.